Tailoring heterogeneities in high-entropy alloys to promote strength–ductility synergy - Evan Ma (Nature Portfolio, 2019)
High entropy alloys are a departure from conventional alloy design. In this review, the authors examine how combinations of hetererogeneities specific to high entropy alloys can overcome the strength–ductility trade-off inherent to traditional alloys.